Development of improved vaccine cell lines against rotavirus - Wu, Weilin (Sci Data, 2017)
Rotavirus is a major cause of severe gastroenteritis among very young children. In developing countries, rotavirus is the major cause of mortality in children under five years old, causing up to 20% of all childhood deaths in countries with high diarrheal disease burden, with more than 90% of these deaths occurring in Africa and Asia. Rotavirus vaccination mimics the first infection without causing illness, thus inducing strong and broad heterotypic immunity against prospective rotavirus infections. Two live vaccines are available, Rotarix and RotaTeq, but vaccination efforts are hampered by high production costs. Here, we present a dataset containing a genome-wide RNA interference (RNAi) screen that identified silencing events that enhanced rotavirus replication. Evaluated against several rotavirus vaccine strains, hits were validated in a Vero vaccine cell line as well as CRISPR/Cas9 generated cells permanently and stably lacking the genes that affect RV replication. Knockout cells were dramatically more permissive to RV replication and permitted an increase in rotavirus replication. These data show a means to improve manufacturing of rotavirus vaccine.